Evaluation of bio-efficacy of field-aged novel long-lasting insecticidal nets (PBO, chlorfenapyr or pyriproxyfen combined with pyrethroid) against Anopheles gambiae (s.s.) in Tanzania - Jackline L. Martin; Louisa A. Messenger; Edmund Bernard; Monica Kisamo; Patric Hape; Osca Sizya; Emmanuel Festo; Wambura Matiku; Victoria Marcel; Elizabeth Malya; Tatu Aziz; Nancy S. Matowo; et al. (Current Research in Parasitology and Vector-Borne Diseases)
Next-generation insecticide-treated bed nets (ITNs) combining two insecticides or an insecticide with a synergist are vital in combating malaria, especially in areas with pyrethroid-resistant mosquitoes where standard pyrethroid long-lasting insecticidal net (LLIN) may be less effective. A community durability study was conducted in Misungwi, Tanzania, during a cluster randomised controlled trial. This study assessed the bio-efficacy of three net brands combining a pyrethroid insecticide and either a synergist PBO for Olyset Plus, or a second insecticide pyriproxyfen for Royal Guard, and chlorfenapyr for Interceptor G2 over three years. These nets were compared to Interceptor, a standard pyrethroid-only net. A total of 1950 nets were enrolled across 10 clusters in each treatment arm. Thirty nets per type were collected every 6 months up to 30 months, with 50 nets sampled at 36 months. WHO cone bioassays and tunnel tests were performed at 0, 12, 24, 30 and 36 months. Both susceptible An. gambiae (s.s.) Kisumu strain and resistant An. gambiae (s.s.) Muleba-Kis strain were exposed. Over 80% of nets tested against the susceptible Kisumu strain met the WHO criteria after three years of community use. In tunnel tests, mortality (72 h) of the resistant Anopheles varied between 52% and 20%, in Interceptor G2 and was higher than standard Interceptor net up to 24 months. Olyset Plus mortality (24 h) ranged between 84% and 33% in tunnel tests with superior efficacy compared to Interceptor at 0, 24 and 36 months. Sterility effects in Royal Guard were higher when these nets were new and at six months but decreased to less than 10% after 12 months. Royal Guard consistently induced higher mortality compared to Interceptor up to 30 months while next-generation ITNs demonstrated higher efficacy in terms of mortality compared to standard LLINs against resistant strains; this superior bio-efficacy did not persist for the full three years. The impact of active ingredient (dual-AI) and PBO diminished relatively quickly. Aside from the initial period when the nets were new, the differences in mortality for Interceptor G2 and Olyset Plus and in sterility for Royal Guard, compared to the standard LLINs, were relatively small thereafter.